(untitled) (Palimpsesto, 2021)
This research proposes a reflection on the reformulation of the communist project that the Spanish. -Mexican philosopher Adolfo Sánchez Vázquez rehearsed in his late work. To do this, it appeals to the considerations of Gerald Cohen regarding the tendencies that Marxism traditionally considered worked in favor of equality: the unbridled development of the productive forces and the unstoppable rise of the working class. The way in which Sánchez Vázquez considered these problems offers clues to the normative challenges Marxism is facing.